ANALISIS KESULITAN MAHASISWA DALAM MENGUASAI TEKNIK GITAR KLASIK PADA PROGRAM STUDI PENDIDIKAN MUSIK - Hernan Chrespo Gultom; Riyan Hidayatullah (Jurnal Manajemen Pendidikan, 2026)
The purpose of this study was to analyze the difficulties students face when learning classical guitar techniques in music education programs. Mastering classical guitar techniques is a crucial skill for music education students because it requires complex technical, musical, and theoretical skills. However, during the learning process, students often encounter various obstacles that prevent them from acquiring these skills. This study used qualitative methods to collect data in the form of a literature review conducted through a review of textbooks, academic journals, research articles, and other academic sources related to classical guitar and music education. The analysis found that students' difficulties generally relate to basic technical aspects such as hand position, fingering, and left/right hand coordination, as well as learning more advanced techniques such as arpeggios, tremolos, and music interpretation. Additionally, other factors contributing to student difficulties include limited practice time, differences in musical backgrounds, a lack of understanding of musical notation, and low learning motivation. The results of this study are expected to serve as material for curriculum evaluation to develop more effective and adaptive classical guitar teaching strategies tailored to the needs of teachers and students, thereby improving the quality of teaching and learning outcomes in music education programs.